Situated or ubiquitous? A segmentation of mobile e–shoppers. (4th October 2013) - Banerjee, Syagnik; Dholakia, Ruby Roy
Extensive wireless internet access via mobile phones, netbooks and tablet computers has eliminated most barriers to ubiquitous consumption. But both practitioners and researchers lack understanding of how availability of wireless internet has translated into flexibility of consumers' internet shopping patterns as well as their receptivity to mobile advertising. Reports show that nations where internet users are more flexible across locations and devices use more media and mobile web for shopping related purposes. In this paper, we identify four segments of consumers that range from 'domestically rooted' who prefer to shop from private spaces to 'flying spenders' who shop across multiple contexts based on their sensitivity to four critical dimensions of the shopping context - place, time, social context and perceived control. These segments differ significantly in the amount of time and money spent online and their readiness to respond to mobile–based advertisements and promotions.